2008
DOI: 10.1007/s11239-008-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nonsteroidal anti-inflammatory drugs on platelet function and severity of upper gastrointestinal haemorrhage

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) cause gastrointestinal (GI) damage primarily due to the inhibition of prostaglandin synthesis in gastric mucosa, which is an important factor in mucosa protection. Platelets are a cardinal feature of vascular repair. A variety of angiogenic stimulators are stored in platelets and are released during clotting at the wound. When there is a defect in any of these functions and/or platelet number, haemostasis is usually impaired and there may be an associated increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…These investigators found no difference in the admission hemoglobin, the source of bleed, the total number of RBC units transfused, ICU admission rate, or length of stay between the 2 groups. Consequently, antiplatelet drugs increased the overall risk score slightly in the study by Pasa et al 6 and increased the likelihood of transfusion in the study by Yong et al 8 In our study and the one by John et al, 9 antiplatelet drugs did not increase the transfusion requirements. Therefore, antiplatelet drugs appear to increase the frequency of GI bleeding in population studies but appear to have a minimal effect on the presentation or course in smaller clinical studies.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…These investigators found no difference in the admission hemoglobin, the source of bleed, the total number of RBC units transfused, ICU admission rate, or length of stay between the 2 groups. Consequently, antiplatelet drugs increased the overall risk score slightly in the study by Pasa et al 6 and increased the likelihood of transfusion in the study by Yong et al 8 In our study and the one by John et al, 9 antiplatelet drugs did not increase the transfusion requirements. Therefore, antiplatelet drugs appear to increase the frequency of GI bleeding in population studies but appear to have a minimal effect on the presentation or course in smaller clinical studies.…”
Section: Discussioncontrasting
confidence: 40%
“…These changes in platelet function could contribute to the severity or outcomes in these patients, but this study did not provide information on outcomes. Pasa et al 6 evaluated patients with upper GI bleeds who were receiving nonsteroidal anti-inflammatory drugs. Seventy-five percent of these patients had decreased platelet function based on in vitro aggregation responses to various platelet agonists.…”
Section: Discussionmentioning
confidence: 99%
“…This observation does not exclude the possibility that NSAID use following a traumatic brain injury can be deleterious. In seniors with gastrointestinal bleeding and a history of NSAID use, 73% had abnormal PFA results and this subgroup had more severe bleeding compared to patients with normal PFA results [18,19].…”
Section: Discussionmentioning
confidence: 92%
“…Improvements of ODI scores were significantly greater in the PV group at 1 and 4 weeks, and patients in the PV group also used less medication. PV provides prompt pain relief, rapid improvements in physical functioning, and a decline in medication‐related complications [21].…”
Section: Discussionmentioning
confidence: 99%